Comparative Assessment of Total-Etch and Universal Dentin Bonding Agents on Marginal Adaptation and Fracture Resistance in Deep Margin Elevation: An In Vitro Study (Asian Journal of Pharmaceutics (AJP), 2025)
Objectives: This study aimed to evaluate and compare the microleakage and fracture resistance of total-etch and universal dentin bonding agents applied to class II cavities with deep marginal elevations. Materials and Methods: Forty extracted mandibular molars with standardized class II cavities and deep margins were selected. The samples were divided into two groups: Group A1 was treated with a total-etch bonding agent (Ivoclar Vivadent Te-econom), whereas Group A2 received a universal bonding agent (Adper Single Bond Universal). Fracture strength testing was performed with a universal testing machine, and bonding failure modes were characterized microscopically with scanning electron microscopy (SEM). Data were analyzed with the independent t-test. Results: The total-etch bonding agent group (mean = 24.65) exhibited a higher fracture resistance than the universal bonding agent group (mean = 16.34), although the difference was not statistically significant (P = 0.375). The SEM analysis showed that the universal bonding agent group had large marginal gaps (17.89–21.04 μm), signifying poorer sealing ability and higher susceptibility to microleakage. Conversely, the groups treated with total-etch bonding agents had smaller marginal gaps, with the smallest recorded being 2.53 μm, which indicates better adaptation and sealing. Conclusion: Total-etch bonding agents presented better resistance to fracture and marginal sealing properties compared with universal bonding agents. While differences in fracture resistance were not statistically significant, better sealing through the total-etch bonding agents and reduced microleakage would indicate improved clinical performance and longevity in the treatment of deep margin cavities.